2023
DOI: 10.1186/s41687-023-00570-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ lived experience and reflections on long COVID: an interpretive phenomenological analysis within an integrated adult primary care psychology NHS service

Abstract: Background Long Covid is an unknown illness which has been shown to affect sufferers regardless of mild initial COVID-19 or age. There is still a lot unknown about long COVID illness. There has been a call to understand this illness not only from a professional standpoint but also through the lived experience of patients. Patient reported outcomes through lived experience research is one such angle. To date, no research has explored the overall lived experiences and long COVID illness trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The participants listed having symptoms like tongue numbness, low blood pressure, coughing out blood, diarrhoea, speaking difficulties, blocked nose, throat obstruction, sleeping difficulties, and breathing difficulties. These symptoms were also corroborated by the participants in the research conducted by Skilbeck et al [41] and Alkaissi et al [42].…”
Section: Discussionsupporting
confidence: 55%
“…The participants listed having symptoms like tongue numbness, low blood pressure, coughing out blood, diarrhoea, speaking difficulties, blocked nose, throat obstruction, sleeping difficulties, and breathing difficulties. These symptoms were also corroborated by the participants in the research conducted by Skilbeck et al [41] and Alkaissi et al [42].…”
Section: Discussionsupporting
confidence: 55%
“…This manuscript also contributes to a growing body of knowledge about the lived experience of long COVID. 5 , 15 19 Among participants, there was a wide variety of symptoms and symptoms patterns. Participants’ symptoms were similar to those reported in other studies of patients with long COVID, including postexertional malaise.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research on the lived experience of PwLC [18 19] including their self-reported barriers to accessing healthcare [13 14]. Until recently, however [15], none have focussed on community rehabilitation.…”
Section: Introductionmentioning
confidence: 99%